The Effectiveness of Inquiry-Based Virtual Laboratories on Students' Physics Creativity: A Systematic Literature Review - Gunawan Gunawan; Lovy Herayanti; Fahmi Yahya; Baiq Nabila Saufika Zainuri; Qothrunnada Qothrunnada (Indonesian Journal of Applied Science and Technology, 2023)
Creativity is a core competency in twenty-first-century science education, and inquiry-based virtual laboratories are increasingly used in physics instruction to foster creativity, particularly where laboratory resources are limited. However, evidence of their effectiveness remains fragmented across study contexts, creativity dimensions, and instructional designs. This systematic literature review synthesizes empirical studies published between 2013 and 2022 on the effectiveness of inquiry-based virtual laboratories in enhancing students' creativity in physics education. Following the PRISMA 2020 guidelines, four databases (Scopus, DOAJ, Crossref, and Google Scholar) were searched, yielding 572 records, of which 42 studies met the inclusion criteria. The findings indicate that inquiry-based virtual laboratories consistently improve students' creativity, with the greatest gains observed in verbal creativity and ideational fluency compared with figural creativity and originality. Much of the available evidence originates from Indonesia, particularly from studies conducted by the University of Mataram research group on electricity, heat, and fluid mechanics. Effectiveness was influenced by the degree of inquiry guidance, the quality of the virtual simulation environment, and the extent to which learning activities scaffolded divergent thinking, whereas evidence regarding gender differences remained inconsistent. Overall, inquiry-based virtual laboratories represent an effective and accessible approach to fostering creativity in physics learning, although broader educational contexts, more standardized creativity measures, and longer-term studies are needed.